Comparative genomic analysis and clinical outcomes of BRAF-mutated advanced biliary tract cancers - Tang, Tin-Yun; Nichetti, Federico; Kaplan, Ben; Lonardi, Sara; Pietrantonio, Filippo; Salvatore, Lisa; Vivaldi, Caterina; Rimassa, Lorenza; de Braud, Filippo; Rizzato, Mario Domenico; Pavlick, Dean; Chu, Randy; et al. (Clinical cancer research, 2023)
PURPOSE: BRAF mutations are rare in biliary tract cancers (BTC), but are of interest given the recent developments in targeted therapy for BTC. We investigated the clinical outcomes in a cohort of BRAF-mutant advanced BTC treated with first-line chemotherapy. Furthermore, we investigated the genomic landscape of BRAF class I, II, and III mutations in the intrahepatic cholangiocarcinoma (iCCA) subgroup of BTC. - EXPERIMENTAL DESIGN: We analyzed two nonoverlapping cohorts. We examined the genomic landscape of BRAF-mutated iCCA in a "genomic cohort" [187 class I, 82 class II, 113 class III BRAF mutants and 8,026 wildtype (WT)]. We also analyzed median progression-free survival (PFS) and overall survival (OS) on first-line chemotherapy in a separate multi-institutional "clinical cohort" of patients with BTC (including iCCA and extrahepatic cholangiocarcinoma (eCCA) and gallbladder cancer; 41 class I, 32 class II+III BRAF mutants and 1,042 WT). - RESULTS: In the entire BTC clinical cohort, the median PFS was shorter for class I [HR, 2.11 (P < 0.001)] and class II+III [HR, 1.72 (P = 0.007)] as compared with BRAF WT. OS was also shorter in class I [HR, 2.04 (P = 0.011)] and class II+III [HR, 1.86 (P = 0.002)] as compared with BRAF WT. In the iCCA subgroup, class I alterations were mutually exclusive with FGFR2, IDH1/2, ERBB2, and KRAS mutations. Class II+III mutations appear to be mutually exclusive with FGFR2 and KRAS. - CONCLUSIONS: In BTC, all classes of BRAF mutations are associated with a worse prognosis. BRAF mutations occur in 5% of iCCA subgroup and may be mutually exclusive with other targetable mutations.
Gesehen am 17.09.2024